2003
DOI: 10.1046/j.1532-5415.2003.51110.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Hip Fracture Morbidity, Mortality and Costs

Abstract: Hip fractures result in significant mortality, morbidity, and costs. The estimated lifetime cost for all hip fractures in the United States in 1997 likely exceeded $20 billion. These results emphasize the importance of current and future interventions to decrease the incidence of hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
534
2
15

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 775 publications
(568 citation statements)
references
References 55 publications
4
534
2
15
Order By: Relevance
“…The risk of clinical fracture (a composite of nonvertebral fracture and symptomatic vertebral fracture) was also significantly lower in the romosozumab group within 12 months after the start of treatment than in the placebo group. Because vertebral and clinical fractures are associated with increased morbidity and considerable health care costs, [16][17][18] a treatment that would reduce this risk rapidly could offer appropriate patients an important benefit. Although all patients made the transition to denosumab in the second year of the trial, the risk of fracture was lower in the group that had received romosozumab in the first year than in the group that had received placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of clinical fracture (a composite of nonvertebral fracture and symptomatic vertebral fracture) was also significantly lower in the romosozumab group within 12 months after the start of treatment than in the placebo group. Because vertebral and clinical fractures are associated with increased morbidity and considerable health care costs, [16][17][18] a treatment that would reduce this risk rapidly could offer appropriate patients an important benefit. Although all patients made the transition to denosumab in the second year of the trial, the risk of fracture was lower in the group that had received romosozumab in the first year than in the group that had received placebo.…”
Section: Discussionmentioning
confidence: 99%
“…(4,64,65) The difference is probably reflecting a difference in comorbidities and health between genders. (66) One-year mortality varies from >50% for male nursing home patients to < 2% for fracture patients below the age of 70.…”
Section: Othermentioning
confidence: 99%
“…(88) Hip fracture patients are major consumers of public health services; however there are considerable international and interregional differences. (8,65,90) Need for health services depend on age, gender, available informal care and organization of health care. (91) In Norway nursing homes are the main institutional service provided by municipalities.…”
Section: Othermentioning
confidence: 99%
“…The incidence of hip fracture has increased worldwide along with the increase in the elderly population. (2)(3)(4) Previous studies have shown that ORIGINAL ARTICLE J JBMR the lifetime risk of hip fracture is 17.5% for women and 6% for men. (5) In the vast majority of cases, a hip fracture is a fragility fracture arising from a fall or minor trauma in individuals with weakened osteoporotic bones, particularly in elderly individuals who are more likely to fall because of poorer balance, medication side effects, and difficulty in maneuvering around environment hazards.…”
Section: Introductionmentioning
confidence: 99%